2018
DOI: 10.3390/challe9010016
|View full text |Cite
|
Sign up to set email alerts
|

What are the Current Priorities and Challenges for (Urban) Soundscape Research?

Abstract: Soundscape research is attracting an ever-increasing worldwide interest from different disciplines and stakeholders. This brief commentary paper aims at offering some insights into the new directions this research (and practice) field will likely go, in the near future. For this purpose, eleven early-career soundscape researchers and practitioners were approached and asked to provide a response to the question "What are the current priorities and challenges for soundscape research?" Five recurring themes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…On the other side, lowering sound pressure levels were proved to be insufficiently effective for achieving acoustic comfort [22]. For these reasons, analyzing perception of both positive and negative sound sources, overall quality of acoustic environments and its relations with non-auditory factors has been largely investigated within the soundscape discourse [23][24][25]. Recently, it has also been looked into finding means of successfully using qualitative and quantitative indicators to achieve acoustically pleasing spaces [6,26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, lowering sound pressure levels were proved to be insufficiently effective for achieving acoustic comfort [22]. For these reasons, analyzing perception of both positive and negative sound sources, overall quality of acoustic environments and its relations with non-auditory factors has been largely investigated within the soundscape discourse [23][24][25]. Recently, it has also been looked into finding means of successfully using qualitative and quantitative indicators to achieve acoustically pleasing spaces [6,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Method A relies on a soundwalk in situ, one of the main soundscape research tools [6,25,26,32]-an act of walking through a setting with a focus on critical listening to the sounds that can be heard there [33]. In an urban environment, its aim is to collect audio data and grasp a mental representation of a city and its public space by combining soundscape with urban morphological features [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…This allows researchers to study the cause-and-effect relationship between dependent and independent variables, but at the likely expense of ecological validity, owing to the artificiality of the controlled virtual acoustic environment. Hence, the quality of acoustic recordings and reproduction techniques plays a vital role in achieving sufficiently high ecological validity under laboratory conditions throughout the soundscape design process [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alternative assessment methods should also be sought. While the body of soundscape literature is still growing steadily, there is limited understanding of what is the (measurable) impact of soundscape science [5]. Thus it is important to explore: "What is the outreach of soundscape research?…”
Section: A Soundscape Framework: From Research To Outreachingmentioning
confidence: 99%
“…Aletta and Xiao [5] reported that more than 2400 soundscape-related papers have been published in peer-reviewed international journals in the last 20 years. Notwithstanding, soundscape has not always been successful at attracting attention from world-wide policy makers and, consequently, awareness among community stakeholders.…”
Section: Introductionmentioning
confidence: 99%